Acute Ethion Exposure Alters Expression of TLR 9 in Lungs of Mice - Verma, Geetika; Ramneek, Ramneek; Mukhopadhyay, C. S.; Sethi, R. S. (Indian Journal of Veterinary Anatomy, 2016)
The present study was conducted to investigate the expression of Toll like receptor (TLR) 9 in lungs of mice following acute ethion exposure with or without lipopolysaccharide (LPS). The animals were divided into two groups viz. treatment and control (n=10; each group). The treatment group-was administered ethion @8 mg kg-1 body weight/day (1/5LD50) orally for 24 hours while control was fed corn oil. At the end of exposure, half animals from both groups were challenged with LPS @ 80Î¼g/animal and other half with normal saline solution.The lung samples were collected in paraformaldehyde for immunohistochemistry and RNA later solution for quantitative real time PCR (qPCR) analysis. LPS resulted strong immunopositive TLR9 reaction in septal and airways epithelialcells. Further, acute exposure to ethion alone or in combination with LPS showed intense immunopositive expression of TLR9.The qPCR analysis revealed that LPS caused 2.76 folds increase in the expression of TLR9 mRNA. Ethion exposure further increased the expression to 6.69 folds. However, ethion followed by LPS resulted 9.52 folds increase in TLR9 mRNA expression. It is the first data on the expression TLR9 following acute exposure to ethion suggesting that ethion alone or in combination with LPS increases the expression of TLR9 mRNAat protein and mRNA levels.